A retrospective analysis from a single center for 60 COVID-19 patients with asymptomatic, mild to moderate, and severe conditions in Wuxi, China. Issue 30 (30th July 2021) - Huang, Jiehui; Qian, Chao; Bian, Tao; Chu, Meiping; Yin, Weiwei; Pang, Yonghua; Bai, Jinmei; Huang, Yanjie
Abstract : Abstract: The aim of this study was to retrospectively analyze the clinical data of COVID-19 patients with different severity during February 2020 in Wuxi, China. The present retrospective study included a total of 60 cases who were diagnosed as COVID-19 patients and hospitalized in the Wuxi Fifth People's Hospital during February 2020 to March 2020. Among all patients 14 cases were asymptomatic, 25 cases were with mild stage, 13 cases were with moderate stage, and 8 cases were with severe stage. Basic clinical data as well as clinical characteristics, including temperature, respiratory rate, heart rate, blood gas analysis data, whole blood test data, and the prognosis condition, were collected and analyzed. Statistical analysis was conducted in different severity stage patients. Among the patients, the median temperature gradually increased from the asymptomatic to the severe patients and the median age increased from the mild to the severe patients with statistical difference. The hospitalization duration was the highest in severe patients. Higher heart rate, as well as lower oxygen partial pressure and oxygenation index were observed in severe patients than the other groups. Besides, higher CRP and globulin levels after admission were found in severe patients, and were gradually increased from the asymptomatic patients to the severe patients. On the contrary, the lymphocyte ratio and count was significant lower in severe patients. We also observed higher D-Dimer levels in the severe patients and the difference was statistical. Among all patients, 2 cases (3.33%) died and other patients were all cured after treatment. Statistical difference was mainly found mainly in age, hospitalization duration, temperature, CRP levels, O2 partial pressure and oxygenation index, globulin, lymphocyte ratio, and D-Dimer in patients with different severity. The higher CRP levels, lower O2 partial pressure and oxygenation index, higher globulin, lower lymphocyte ratio, and higher D-Dimer might be associated with the patients' severity.